Highlights of dense magnetized plasma research in Poland - Sadowski, M.J.; Scholz, M. (Національний науковий центр «Харківський фізико-технічний інститут» НАН України, 2010)
This invited lecture presents the most important achievements of theoretical and experimental studies which concerned dense magnetized plasmas and were performed in Poland during recent few years. Those studies were concentrated on high-current pulse discharges within the large mega-joule PF-1000 facility, which was operated at the IPPLM in Warsaw and investigated by researchers from the IPJ and IPPLM. The machine was operated mainly with a pure D2 filling, and the peak discharge current amounted to 1,5...1,8 MA. Theoretical studies concerned motions of accelerated primary deuterons and fusion-produced protons. Experimental investigations included a multi-frame laser interferometry, measurements of neutron yields, optical spectroscopy of plasma streams, diagnostics of fast electronand ion-streams, and measurements of an angular distribution of fusion protons.